Cost analysis of drugs used in management of heart failure with reduced ejection fraction and marketed in India - Tupe, Daya; Bhave, Kiran; Pandit, Prasad (International Journal of Basic & Clinical Pharmacology, 2024)
Background: Heart failure is characterised by significant morbidity, mortality, poor functional capacity, reduced quality of life, and high cost of lifelong medications. No studies have been performed yet on cost analysis of oral drugs used in management of HFrEF (Heart Failure with Reduced Ejection Fraction). So, we analysed cost variations of different brands of such drugs which are marketed in India. Methods: It was an analytical study in which maximum and minimum costs in rupees per 10 tablets/capsules of each drug in same strength, manufactured by different pharmaceutical companies in India, were obtained from “Current Index of Medical Specialties” (CIMS) January to April 2023, Indian Drug Review (IDR 2023) and Drug Today (January– April 2023 Cost ratio and % cost variation were calculated for each drug. % Cost variation= Maximum cost- Minimum cost × 100/ Minimum cost. Cost ratio= Price of the costliest brand/ Price of the least costly brand. Results: Totally 652 brands of HFrEF management drugs from different classes were evaluated. Telmisartan 80 mg had highest cost ratio of 44 and 4300% cost variation, while Spironolactone 25 mg had lowest cost ratio of 1.29 and 31.11% cost variation. Conclusions: Our study showed significant cost variation in different brands of the same drugs that are used in the management of HFrEF. To lessen economic burden and to improve adherence to treatment, also considering the demographics, it is desirable for doctors to prescribe least costly brands/ generic drugs, to meet the health-care needs of such patients.